2016
DOI: 10.1097/iae.0000000000000691
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective Review of Lucentis “Treat and Extend” Patterns and Outcomes in Age-Related Macular Degeneration

Abstract: Treat and Extend dosing regimen allows similar visual outcomes to monthly dosing, while reducing the total number of injections, visits, and overall cost.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…In contrast, based on clinical reports, a proactive T&E regimen has been shown to provide better functional outcomes than a PRN regimen with fewer treatment visits and with a mean of approximately 6 to 8 injections during the first year of treatment. 18,23,33,34 To summarize, ranibizumab 0.5 mg administered according to a T&E regimen was statistically noninferior and clinically comparable with a ranibizumab monthly regimen in improving VA from baseline to the end of study in patients with nAMD. Patients in both treatment groups achieved a rapid initial gain in BCVA, which was maintained up to the end of study.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…In contrast, based on clinical reports, a proactive T&E regimen has been shown to provide better functional outcomes than a PRN regimen with fewer treatment visits and with a mean of approximately 6 to 8 injections during the first year of treatment. 18,23,33,34 To summarize, ranibizumab 0.5 mg administered according to a T&E regimen was statistically noninferior and clinically comparable with a ranibizumab monthly regimen in improving VA from baseline to the end of study in patients with nAMD. Patients in both treatment groups achieved a rapid initial gain in BCVA, which was maintained up to the end of study.…”
Section: Discussionmentioning
confidence: 93%
“…It offers opportunities to individualize patient management while minimizing treatment burden and costs associated with patient care. 33…”
Section: Discussionmentioning
confidence: 99%
“…The TREX-AMD trial included 60 patients (2:1 randomization to T&E and monthly) and by the end of year 2, many data points were missing . All other T&E trials are either prospective or retrospective single-arm trials or noncontrolled studies looking at different T&E regimens to determine whether VA outcomes are not worse compared with monthly treatment. Hence, there is a need for large randomized clinical trials comparing the T&E approach with monthly treatment beyond 12 months.…”
Section: Introductionmentioning
confidence: 99%
“…The comparative efficacy between TAE and fixed monthly administration has also been described in numerous other studies, both retrospectively and prospectively. For example, Chen et al demonstrated in a retrospective analysis that eyes undergoing monthly vs. TAE treatment at 1 year on average had a visual difference of −0.5 letters (p = 0.81) [47]. Additionally, Abedi et al demonstrated in a prospective cohort study of 120 eyes, average visual gains of 9.5 letters and 8.0 letters at 12 and 24 months, respectively, which were comparable to those of the pivotal clinical trials [48].…”
Section: Treat-and-extend (Tae) and Treat-extend-stop (Tes) Methodsmentioning
confidence: 99%